Efektivitas Terapi Storytelling untuk Mengurangi Tingkat Agresi pada Anak TK Aisyiyah VI Padang - Putri, Dea Fenny Kirana; Ananta, Aditya Briliant; Novita, Dita; Aulia, Prima (Asian Journal of Early Childhood and Elementary Education, 2024)
This study explores aggression behavior in early childhood and the effectiveness of storytelling in reducing it using quantitative methods. Data were collected through observation and questionnaires at Aisyiyah VI Kindergarten in Padang, with data analysis using JASP 0.16.4.0. Aggression, defined as behavior aimed at causing harm, is increasingly common among children in Indonesia and can be both physical and verbal. Storytelling was studied as a potential intervention, with evidence showing improved social behavior and decreased aggressiveness. The technique involves using stories that are appropriate to the child's developmental stage and allows them to learn through the example of the characters in the story. The implementation process includes needs analysis, theme determination, story creation and delivery. The results show storytelling is effective in reducing aggressive behavior in early childhood. This study highlights the important role of parents and teachers in supporting children's social development through a comprehensive educational approach.